Copper in soils, plants and ruminant animal nutrition with special reference to sub-Saharan Africa - Haque, I.; Aduayi, E.A.; Sibanda, S. (International Livestock Centre for Africa, 1992)
Examines the present status of research on copper (Cu) in the soil, plant and ruminant animal system in sub-Saharan Africa with emphasis on forage crops. The soil content of total and available Cu and the distribution of Cu in the soil profile are demonstrated. The biochemical role of Cu in the plant and diagnostic criteria for detecting Cu deficiency, adequacy and toxicity were reviewed. The need to ensure adequate Cu in the soil and plant to provide micronutrient requirements for ruminant animals is stressed.